STRATEGI MENERJEMAHKAN WACANA BAHASA JEPANG KE DALAM BAHASA INDONESIA DENGAN MENGGUNAKAN GOOGLE TRANSLATE OLEH MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Resi Silaturrahmi; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study discusses the strategy of translating Japanese discourse into Indonesian by Japanese Education Department Riau University. 60 data were collected from 2 discourse whuch will be translated by 30 students. They were asked to translated discourse on sports and social themes using Google Translate. This research using the translation strategy theory proposed by Suryawinata & Hariyanto (2003: 67), addition, deletion, transposition, borrowing, komponential analysis, synonymy and modulation, by Gambier (2006), deletion, addition and substitution and translation procedures by Newmark (1998) (transposition, modulation, adaptation, contextual conditioning, transference and functional conditioning). Findings showed that the students tended to use the transposition and substitution strategy in their translation. This affected the quality of the translation, making it less natural in the target language. In addition, there was mistranslation due to inaccurate/wrong word choices, causing the messages within the source text to fail to be conveyed. This study is hoped to bring valuableinput for the translation studies and courses in the future.Key Words: Translation Strategy, Google Translate.